Role of Histamine as a Peripheral Sympathetic Neuromediator and its Interrelation with Substance P - Atencio, Augusto S. Manzo; de Manzo, Flor A. Pérez; Velasco, Manuel (Current Pharmaceutical Design, 2020)
This article is an educational review about the fundamental aspects related to the proposal of the existence of a peripheral sympathetic reflex regulated by histamine, through its effect on presynaptic H3 type receptors, under the interaction of a sensory neuron that would be mediated by Substance P. In this respect, we consider it useful to highlight the role of histamine, so we discuss some aspects about its history, metabolism, and function, as well as its interaction with H3 type receptors that are considered as neuroreceptors, which define and typify it as a neuromediator at both levels of the nervous system, central and peripheral.
Keywords: substance P